EFFECTIVENESS OF ROLLING MASSAGE AND COMPRESS TECHNIQUES WARM TO BREAST MILK EXPENDITURE IN MOTHERS POST SECTION CAESARIA - Fatmawati, Lilis; Rizka Laily, Nurul Fahmi; Ilmiyah, Nahdiyatul (Indonesian Midwifery and Health Sciences Journal, 2025)
Background. Inadequate breastfeeding is a problem often experienced by mothers who are breastfeeding. Breast milk release time in post sectio caesarean mothers is later than normal postpartum mothers. This study aims to determine the rolling massage technique and warm compresses on breast milk production in post-section caesaria mothers at hospital Denisa. Method. The research design of this study is Quasy Experimental with design (pre post test design). Purposive sampling method. The sample taken was 28 respondents. Divided into 2 groups, 14 respondents were intervened with rolling massage techniques and 14 respondents get warm compresses. Independent variables were rolling massage techniques and warm compresses. The dependent variable is breast milk production in post-section caesarea mothers. Data collection was using the SOP (Standard Operating Procedure) rolling massage technique, warm compress SOP and questionnaire sheet. Result. Wilcoxon test results p-value = 0.001 for breast milk production in the rolling massage technique. Rolling massage technique means there is an influence on breast milk production. The Wilcoxon test result p value = 0.001 for the result of Wilcoxon test showed that the p-value = 0.001 for breast milk production on warm compress means that there is an effect on breast milk production. The Mann Whitney U Test statistical test results obtained a significance value of p = 0.009 so that there is a difference between rolling massage and warm compress techniques on breast milk production. Conclusion.  The rolling massage technique and warm compress can be used as a therapy for breast milk production.